2013
DOI: 10.1038/ncomms2401
|View full text |Cite
|
Sign up to set email alerts
|

Spatial separation of photogenerated electrons and holes among {010} and {110} crystal facets of BiVO4

Abstract: Charge separation is crucial for increasing the activity of semiconductor-based photocatalysts, especially in water splitting reactions. Here we show, using monoclinic bismuth vanadate crystal as a model photocatalyst, that efficient charge separation can be achieved on different crystal facets, as evidenced by the reduction reaction with photogenerated electrons and oxidation reaction with photogenerated holes, which take place separately on the {010} and {110} facets under photo-irradiation. Based on this fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
1,273
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,615 publications
(1,336 citation statements)
references
References 59 publications
53
1,273
5
5
Order By: Relevance
“…Recently, numerous studies are focused on the formation of heterogeneous structures by rational growing supported substances (typically noble metal nanoparticles) on the support (typically metal oxides), since metal oxides can not only serve as a support for a better dispersibility of disperse metal nanoparticles (NPs), but also enhance the catalytic abilities by interacting with the metal NPs 6, 27, 30, 33, 36, 40, 50, 61, 145, 146, 147. Despite many successful examples on the synthesis of heterogeneous structures, it is noteworthy that the spatially controllable deposition of noble metal NPs on metal oxide support is a significant topic.…”
Section: Facet‐controlled Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, numerous studies are focused on the formation of heterogeneous structures by rational growing supported substances (typically noble metal nanoparticles) on the support (typically metal oxides), since metal oxides can not only serve as a support for a better dispersibility of disperse metal nanoparticles (NPs), but also enhance the catalytic abilities by interacting with the metal NPs 6, 27, 30, 33, 36, 40, 50, 61, 145, 146, 147. Despite many successful examples on the synthesis of heterogeneous structures, it is noteworthy that the spatially controllable deposition of noble metal NPs on metal oxide support is a significant topic.…”
Section: Facet‐controlled Depositionmentioning
confidence: 99%
“…It is noteworthy that, although high‐index facets that have high‐density atomic edges with corners and plentiful unsaturated active sites are promising for catalysis and sensing applications, those facets are often unstable, and hardly obtained by traditional chemical methods 17, 18, 19, 20, 21, 22, 23. Thus, the shape‐dependent catalysis and sensing behaviours is primarily focused on NCs enclosed by low‐index facets, especially the three basic facets (i. e., the {100}, {111}, and {110} facets) 6, 7, 8, 9, 12, 13, 14, 16, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34. For instance, by employing hydrofluoric acid as a capping agent (CA), H. G. Yang et al34 were the first to obtain uniform anatase TiO 2 single crystals with a high percentage (47%) of highly reactive {001} facets, which possessed promising applications in sensors, solar cells and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the performance of the semiconductor-based water splitting reaction, researchers have proposed numerous strategies for designing more efficient photocatalysts, e.g., by forming nanoscale heterojunctions, modulating the size, shape, and crystal structure of photocatalysts, and doping additional elements. [107][108][109][110][111][112][113][114] These strategies can provide highly efficient photocatalysts for the water splitting reaction by inhibiting the recombination of electronhole pairs, reducing and optimizing the migration distance of charge carriers, and tuning the band structure. However, these impressive achievements are still not adequate enough to be applied for practical use.…”
Section: Water Splittingmentioning
confidence: 99%
“…[21][22] It has also been reported that the photoelectrochemical reactivity of BiVO4 can be strongly modulated by the exposed crystal facet. 23 We have recently reported a rate law analysis of the kinetics of water oxidation on hematite photoanodes as a function of the density of surface accumulated valence band holes. This study showed a transition from 1 st order behavior at low light flux to 3 rd order at higher light fluxes.…”
Section: Toc Graphicsmentioning
confidence: 99%